STATE’S LEGAL PROTECTION TO COPYRIGHT HOLDERS OF SONGS IN RELATION TO THE ONLINE SONGS PIRACY - Nanda Reza Putra Pratama; Zenny Rezania Dewantary (Problematika Hukum, 2017)
Indonesia has a law regulating about copyright, namely Law No. 28 Year 2014 on Copyright. This law gives legal protection towards copyright infringements. However, the number of piracy of songs through online sources has been increasing rapidly. Song is a subject under copyright concept, hence, is protected by the copyright law. The piracy of songs gave disadvantage for the song writer, the singer, the recording label, and other related parties. This irresponsible behavior is difficult to tackle because of it is conducted online and free and netizens somehow are capable to pirate songs no matter how it is banned. This situation leads to the question on how the Indonesian government provides the protection and conduct to eradicate piracy of songs through internet.